Absence of neutralizing antibodies against the Omicron SARS-CoV-2 variant in convalescent sera from individuals infected with the ancestral SARS-CoV-2 virus or its Gamma variant (Clinics, 2022)
Objectives: The aim of the present study was to evaluate if neutralizing antibody responses induced by infection with the SARS-CoV-2 strain that was dominant at the beginning of the pandemic or by the Gamma variant was effective against the Omicron variant.Methods: Convalescent sera from 109 individuals, never exposed to a SARS-CoV-2 vaccine, who had mild or moderate symptoms not requiring hospitalization following either a documented SARS-CoV-2 ancestral strain infection or a Gamma variant infection, were assayed for in vitro neutralizing antibody activity against their original strains and the Omicron variant.Results: Following an infection with the ancestral strain, 56 (93.3%), 45 (77.6%) and 1 (1.7%) serum sample were positive for neutralizing antibodies against the ancestral, Gamma variant, and Omicron variant, respectively. After infection with the Gamma variant, 43 (87.8%) and 2 (4.1%) sera were positive for neutralizing antibodies against the Gamma and Omicron variants, respectively.Conclusions: Neutralizing antibodies generated following mild or moderate infection with the SARS-CoV-2 ancestral strain or the Gamma variant are not protective against the Omicron variant.